1977
DOI: 10.1093/ajcn/30.5.728
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E status of Chinese population in Taiwan

Abstract: Vitamin E status of Chinese population with different age groups was studied by determining plasma vitamin E levels (PE) and hydrogen peroxide-induced erythrocyte hemolysis (HPEH). The mean PE of 99 adults, ages 23 to 78, was 1.05 +/- 0.47 mg/100 ml. There was no significant difference between sexes. PE was negatively correlated with HPEH (P less than 0.01). There was a significant positive correlation (P less than 0.01) between PE and plasma cholesterol level. The mean PE of four young men of Yami tribesmen, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1979
1979
1994
1994

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…High levels of serum vitamin A are found to be associated with male sex in humans (Comstock et al, 1987). Serum vitamin E levels were found to increase gradually with age (Leitner er al., 1960;Desai and Lee, 1974;Chen et al, 1977). The association of serum levels of vitamin A with age has also been reported in various studies (Abraham et al, 1974;Friedman et al, 1986;Ahmed et al, 1992).…”
Section: Introductionmentioning
confidence: 72%
“…High levels of serum vitamin A are found to be associated with male sex in humans (Comstock et al, 1987). Serum vitamin E levels were found to increase gradually with age (Leitner er al., 1960;Desai and Lee, 1974;Chen et al, 1977). The association of serum levels of vitamin A with age has also been reported in various studies (Abraham et al, 1974;Friedman et al, 1986;Ahmed et al, 1992).…”
Section: Introductionmentioning
confidence: 72%
“…Vitamin E The plasma level of vitamin E was found to increase gradually with age up to the seventh decade in several earlier studies (10,11). However, other studies have failed to show any relationship of age to plasma vitamin E levels (17), and some studies have even demonstrated a decline in vitamin E levels after the age of 65 (12)(13)(14)(15).…”
Section: And Discussionmentioning
confidence: 87%